Optimization of Operating Conditions in Lignin Isolation Process of Rice Straw Using Box-Behnken Design Methodology - Anggerta, Lintang Alivia; Dewi, Listiyana Candra (Jurnal Teknik Kimia dan Lingkungan, 2025)
Exposure to sunlight causes ultraviolet (UV) radiation, which can damage the body cells. Those negative effects can be prevented by using sunscreen, which contains lignin. Lignin has been proven to absorb or reflect      UV radiation effectively. Rice straw was being used as a non-synthetic active ingredient in sunscreen production. This research shows that during the operating conditions of the isolation process, several variables affect yield production, such as the mass of rice straw, temperature and time of isolation. Therefore, this research was carried out to optimize the lignin isolation process using the Box-Behnken Design (BBD) methodology.  Rice straw dregs that have undergone sample preparation were subsequently isolated through hydrolysis using 5% (w/v) NaOH. After that, the product was carried out to the next process, namely acidification, which used 72% (v/v) H2SO4. The resulting precipitate was then filtered and dried in an oven. Subsequently, the fiber content of the product was analyzed using the Van Soest analysis method, while the process conditions were evaluated using the BBD methodology. In this research, the highest lignin yield obtained was 17.04%, and the optimal process conditions used were 30 g mass of straw, 140°C, and 3 hours reaction time.